Bilateral nevus of Ota - Mehta, Vandana; Balachandran, C. (Journal of Pakistan Association of Dermatologists, 2016)
Nevus of Ota is a dermal melanocytosis seen in the distribution of ophthalmic, maxillary and mandibular divisions of the trigeminal nerve. Most of the cases reported are in females with a typical unilateral distribution. We describe a case of bilateral nevus of Ota in a male. Â